ANALYSIS OF THE FEASIBILITY OF USING EMERGING TECHNOLOGIES TO ASSIST ACCESSIBILITY IN ELECTRONIC GAMES - Santos, Fernando Felipe dos; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2024)
This article investigates the feasibility of using emerging technologies to promote accessibility in video games, focusing primarily on the needs of players with visual, auditory, motor, and cognitive impairments. Through a literature review and analysis of technologies such as artificial intelligence, virtual reality, and augmented reality, the study assesses the impact of these innovations on the development of inclusive games. The results indicate that these technologies can significantly improve accessibility, providing experiences tailored to the different limitations of players. However, challenges remain, such as the high cost of implementation and the lack of standardization in accessible design. It is concluded that, despite the difficulties, these technologies have great potential to assist and transform the current video game landscape, fostering broader inclusion. Furthermore, recommendations are proposed to facilitate the integration of these solutions into the process of creating accessible games, ensuring greater equity in access to digital entertainment through video games.
Keywords: Accessibility; Emerging technologies; . Electronic games; Inclusion